THE EFFECT OF MARKETING STRATEGY AND SERVICE QUALITY ON CONSUMER SATISFACTION IN THE NUANCES OF COFFE JEMBER - Sinta, Dewi; Ahmad Izzuddin; Septy Holisa Umami (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to find out and analyze the influence of marketing strategy and service quality on consumer satisfaction in the Nuansa Coffe Jember. Method: This type of research uses a quantitative method with a sample of 80 respondents and uses a Non-probability sampling technique with a purposive sampling technique, using a data collection technique in the form of a questionnaire to the respondents. The data analysis techniques of this study use instrument testing, classical assumptions, multiple linear regression, hypothesis tests, and R2 determination coefficients. Results: The results of the analysis obtained showed that marketing strategy and service quality had a significant effect partially on consumer satisfaction in the Nuansa Coffe Jember. The results of the R2 determination coefficient test were 0.539 or 54% of the influence contribution level. Novelty: This study provides empirical evidence on the impact of marketing strategy and service quality on consumer satisfaction in the context of Nuansa Coffe Jember, contributing to the understanding of consumer behavior in the coffee shop industry.